Tantangan Terhadap Pelaksanaan Demokrasi Pancasila di Era Digital - Afra Mudrikah; Eka Fajri Jayanti; Tasya Chika Setiaulia; Teuku Aditya Rian Syaputra; Hamdi Abdullah Hasibuan (Pusat Riset dan Inovasi Nasional, 2024)
This article aims to discuss the challenges of democracy in the digital era. Pancasila democracy is defined as a democratic system based on the values contained in Pancasila, using law to govern a democratic state. The legal regulations established to govern the state must align with the goals and worldview of the nation so that an effective and contextually appropriate democratic system can be properly implemented. The method used in this research is qualitative research with a case study approach, examining various sources such as scholarly journals, books, and articles related to the challenges of Pancasila democracy in the digital era. The research findings indicate that Pancasila democracy faces challenges in the digital era, and solutions are necessary to address these challenges. This article also discusses the role of education in strengthening Pancasila democracy in the digital era.